2016
DOI: 10.1002/ppul.23562
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of 645 children with parapneumonic effusion and empyema—A German nationwide surveillance study

Abstract: SummaryObjective: To evaluate the initial management of pediatric parapneumonic effusion or pleural empyema (PPE/PE) with regard to length of hospital stay (LOS). Methods: Collection of pediatric PPE/PE cases using a nationwide surveillance system (ESPED) from 10/2010 to 06/2013, in all German pediatric hospitals. Inclusion of PPE/PE patients <18 years of age requiring drainage or with a PPE/PE persistence >7 days. Staging of PPE/PE based on reported pleural sonographic imaging. Comparison of LOS after diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 25 publications
1
36
2
4
Order By: Relevance
“…In a national surveillance study in Germany examining the treatment of 645 children with parapneumonic effusion/empyema over nearly three years, less than a quarter required invasive intervention with only 89 receiving a chest drain with intrapleural fibrinolysis and 43 a surgical procedure (either video-assisted thoracoscopic surgery or an open thoracotomy). There were no significant differences in the length of stay between surgical and drain patients [16]. …”
Section: Discussionmentioning
confidence: 99%
“…In a national surveillance study in Germany examining the treatment of 645 children with parapneumonic effusion/empyema over nearly three years, less than a quarter required invasive intervention with only 89 receiving a chest drain with intrapleural fibrinolysis and 43 a surgical procedure (either video-assisted thoracoscopic surgery or an open thoracotomy). There were no significant differences in the length of stay between surgical and drain patients [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there were no differences in length of stay, total days of antibiotics, or duration of fever between patients treated conservatively, compared to those treated with chest tubes with or without fibrinolysis. Similarly, in a 3‐year prospective, observational study in Germany, Segerer et al found no difference in length of hospital stay among children with effusion or empyema whether they were initially treated invasively (thoracentesis, chest tubes, or video‐assisted thoracoscopic surgery) or non‐invasively (antibiotics only).…”
Section: Introductionmentioning
confidence: 95%
“…59 As referenced above, a nationwide prospective, observational study in Germany found no difference in length of hospital stay among children with effusion or empyema whether they were initially treated invasively (thoracentesis, chest tubes, surgical drainage procedures) or not. 50 Chang et al 60 Mycobacterium tuberculosis is the leading cause of death worldwide from a single bacterial pathogen. 63 The World Health…”
Section: Respiratory Syncytial Virus (Rsv) Infection In Infants and Ymentioning
confidence: 99%
See 1 more Smart Citation
“…All abstracts were reviewed; four prospective randomised studies were identified. We did not consider studies that compared VATS with chest drain without fibrinolytics1 or national surveillance studies 2. All references in these papers were reviewed, and no further relevant papers were found.…”
Section: Searchmentioning
confidence: 99%